Comparison of the Time Use Between Mothers of Blind and Healthy Children in Tehran, Iran - Narges Mahvari; Navid Mirzakhany; Mehdi Rezaee; Seyed Mehdi Tabatabaee; Hamidreza Faghihi (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: The presence of a blind child in the family puts a lot of pressure on the caregivers, especially the mother. Therefore, the mother's mental and emotional condition is affected and disturbs her ability to balance time. By knowing the pattern of time use in mothers of blind children, it is possible to help improve the health and quality of life of these mothers. This study aims to evaluate the time use in mothers of children with blindness compared to the mothers of healthy children.Methods: This is a descriptive and cross-sectional study. Ninety mothers of blind and healthy children aged 6-14 years participated in this study. Mothers were selected from among those whose children were in exceptional schools of Shahid Mohebi, Narjes, and Khazaeili and normal schools in West of Tehran, Iran using a convenience sampling method. Mothers' time use for different activities was evaluated by the Persian version of the Mothers' time Use questionnaire. The collected data were analyzed in SPSS software versio 21 using independent t-test and Mann-Whitney U test.Results: Mothers of children with blindness spent more time on household chores and childcare and less time on sleeping/resting compared to the mothers of healthy children (50.0≥P).Conclusion: The presence of a blind child in the family affects the ability of mothers in balancing the time and the quality of the time spent by them on daily activities. Therefore, there is a need to pay attention to balance of time as a variable of health and quality of life.